2020
DOI: 10.1037/fsh0000459
|View full text |Cite
|
Sign up to set email alerts
|

Linking family and intimate partner relationships to chronic pain: An application of the biobehavioral family model.

Abstract: Introduction:Research is needed to determine mechanisms of effect linking family relationships and chronic pain for adults. Guided by the Biobehavioral Family Model (BBFM), the present study examined indirect effects between a negative family emotional climate and chronic pain disease activity, as mediated by biobehavioral reactivity. Method: Data for this study are from the Midlife Development in the United States; specifically, a subsample of participants who reported experiencing chronic pain (n ϭ 1,461, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…For instance, experiences of loss were mentioned for the values: "family", "intimate relations", and "friends", thus reflecting a high impact on individuals' lives; caring for a loved one was mentioned within the values "family" and "intimate relations"; and, dissatisfaction both with "friends" and "intimate relations" was reported. These results are consistent with other studies reported in the literature, where both family and social life related stressors [45][46][47] were repeatedly observed in chronic back pain patients as was family-related negative strain [46,48,49]. The association between family strain and back pain has also been found to be mediated by depression [50].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, experiences of loss were mentioned for the values: "family", "intimate relations", and "friends", thus reflecting a high impact on individuals' lives; caring for a loved one was mentioned within the values "family" and "intimate relations"; and, dissatisfaction both with "friends" and "intimate relations" was reported. These results are consistent with other studies reported in the literature, where both family and social life related stressors [45][46][47] were repeatedly observed in chronic back pain patients as was family-related negative strain [46,48,49]. The association between family strain and back pain has also been found to be mediated by depression [50].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have now substantiated the role of both intimate partner relationships as well as non-intimate family relationships in understanding the impact of family on health for adults [e.g., ( 33 , 34 )]. Though both operationalizations of family emotional climate—the positivity or negativity, and intensity, of intimate partnerships and of non-intimate family relationships—have been significantly linked to disease activity in tests of the BBFM, studies have tended to support more powerful links for non-intimate family relationships, especially when negative and intense [e.g., ( 29 , 35 , 36 )].…”
Section: Bbfm Applied To Adult Healthmentioning
confidence: 99%
“…We created a latent construct to represent emotion dysregulation by employing two validated indexes on depression (EURO-D) and anxiety (reduced Beck’s Anxiety Inventory, BAI) measured at T2 (Cronbach’s α = 0.764), similar to previous studies using the BBFM [ 30 , 61 ]. In our model, biobehavioral reactivity was conceptualized as a second mediator.…”
Section: Methodsmentioning
confidence: 99%